Methodical approaches to the development of indicators for the use and protection of water resources for the implementation of sustainable development goals in the Republic of Belarus - Dubianok, Sniazhana A.; Kulakou, Andrei Ju. (Journal of the Belarusian State University. Ecology, 2020)
Currently, the Republic of Belarus is actively engaged in the implementation of the Sustainable Development Goals adopted by the UN General Assembly in 2015. The article presents the results of a study on the development of national methods for generating indicators for targets 6.3–6.5 of SDG 6 «Ensuring availability and sustainable management of water and sanitation for all».
Keywords: sustainable development goals; water resources; water use; wastewater; state water cadaster